Functional connectivity within sensorimotor cortical and striatal regions is regulated by sepsis in a sex-dependent manner - Quan Vo; Zachary D. Simon; Gwoncheol Park; Dina C Nacionales; Carmelina Gorski; Evan L Barrios; Gemma Casadesus; Philip A Efron; Lyle L Moldawer; Ravinder Nagpal; Paramita Chakrabarty; Marcelo Febo (NeuroImage)
Sepsis is a state of systemic immune dysregulation and organ failure that is frequently associated with severe brain disability. Epidemiological studies have indicated that younger females have better prognosis and clinical outcomes relative to males, though the sex-dependent response of the brain to sepsis during post-sepsis recovery remains largely uncharacterized. Using a modified polymicrobial intra-abdominal murine model of surgical sepsis, we characterized the acute effects of intra-abdominal sepsis on peripheral inflammation, brain inflammation and brain functional connectivity in young adult mice of both sexes. Following sepsis, both male and female mice survived the procedure, regained body weight within 7 days post-sepsis and showed reduced diversity in their gut microbiome. Interestingly, compared to the sepsis-induced changes observed in female mice, the post-septic male mice exhibited a comparatively robust profile of splenic cell expansion and intracerebral glial proliferation relative to their healthy counterparts. Analysis of resting-state functional Magnetic Resonance Imaging (fMRI) data collected from the post-septic mice revealed that while connectivity to the somatosensory cortex were affected equally in both sexes, intra-network connectivity strength in the striatum preferentially increased in post-septic males but remained near baseline in post-septic female mice. Additionally, the female mice showed reduced network connectivity alterations in the projections from periaqueductal gray to the superior colliculus as also between the anterior cingulate cortex and the striatum. Coupled with the sustained intracerebral gliosis response, the intra-striatal fMRI response patterns in males could signify a delayed recovery from sepsis. Together, our study provides evidence that peripheral sepsis influences peripheral immunity, brain immunity and brain connectivity in a sex-dependent manner, with the fMRI response strongly indicating cognitive benefits in young females recovering from sepsis relative to their male counterparts.